2009
DOI: 10.1073/pnas.0911895106
|View full text |Cite
|
Sign up to set email alerts
|

A progeria mutation reveals functions for lamin A in nuclear assembly, architecture, and chromosome organization

Abstract: Numerous mutations in the humancomprising the major structural components of the nuclear lamina, the fibrous meshwork underlying the inner nuclear membrane (1). They are major determinants of nuclear size and shape and are involved in essential functions such as DNA replication and transcription (1). Lamins A (LA) and C (LC) are alternatively spliced products of the LMNA gene, whereas lamins LB1 and LB2 are encoded by LMNB1 and LMNB2. Structurally, the lamins have a conserved central ␣-helical rod domain flank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
216
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 199 publications
(233 citation statements)
references
References 47 publications
15
216
1
1
Order By: Relevance
“…For example, it was reported that the expression of lamin A (E145K progeria mutation) induced the formation of blebs in the nuclear membrane in which lamin B1 was excluded. 30 Another studies show that deletion of lamin B1 increases the size of the Lamin A/C meshwork and induces the formation of lamin A/C-rich and lamin B2-deficient NE blebs 32 23,[33][34][35][36] In contrast with HGP fibroblasts, the telomere length in hematopoietic cells, which typically do not express lamin A, was within the normal range in different HGPS patients' samples. These results suggest that expression of mutant lamin A is necessary for telomere loss in HGPS.…”
Section: Lamin Levels Must Be Tightly Controlled For the Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was reported that the expression of lamin A (E145K progeria mutation) induced the formation of blebs in the nuclear membrane in which lamin B1 was excluded. 30 Another studies show that deletion of lamin B1 increases the size of the Lamin A/C meshwork and induces the formation of lamin A/C-rich and lamin B2-deficient NE blebs 32 23,[33][34][35][36] In contrast with HGP fibroblasts, the telomere length in hematopoietic cells, which typically do not express lamin A, was within the normal range in different HGPS patients' samples. These results suggest that expression of mutant lamin A is necessary for telomere loss in HGPS.…”
Section: Lamin Levels Must Be Tightly Controlled For the Maintenancementioning
confidence: 99%
“…Interestingly, we, and other have shown that the overexpression of lamin B1 leads to NSA. 13,28,30 Particularly, A-T cells exhibit an accumulation of lamin B1 protein, alterations in nuclear architecture and premature senescence. Importantly, we show that the overexpression of lamin B1 in normal cells is sufficient to induce NSA and senescence.…”
Section: Lamin Levels Must Be Tightly Controlled For the Maintenancementioning
confidence: 99%
“…For details, see references Bonne et al, 1999, Cowan et al, 2010, Speckman et al, 2000and Taimen et al, 2009. (n=18) and 1.59×10 −10 (n=38) in (C) and 0.31 (n=17), 0.75 (n=25), 0.03 (n=26), 9.44×10 −6 (n=21) and 0.08 (n=21) in (D) for EV, R460C, lmn-1 RNAi, Q159K and L535P, respectively.…”
Section: Nuclear Response To Mechanical Strain In Living C Elegansmentioning
confidence: 99%
“…LMNB1 is reduced in HGPS cells and declines in normal fibroblasts as they enter replicative senescence (Scaffidi and Misteli, 2005;Taimen et al, 2009;Shimi et al, 2011;Zhang et al, 2011;Freund et al, 2012). Shimi et al (2011) reported that LMNB1 reduction triggered senescence, whereas its overexpression delayed senescence.…”
Section: Introductionmentioning
confidence: 99%